2020
DOI: 10.4240/wjgs.v12.i8.355
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting beads transarterial chemoembolization sequentially combined with radiofrequency ablation in the treatment of untreated and recurrent hepatocellular carcinoma

Abstract: BACKGROUND Drug-eluting beads transarterial chemoem-bolization (DEB-TACE) has the advantages of slow and steady release, high local concentration, and low incidence of adverse drug reactions compared to the traditional TACE. DEB-TACE combined with sequentially ultrasound-guided radiofrequency ablation (RFA) therapy has strong anti-cancer effects and little side effects, but there are fewer related long-term studies until now. AIM To explore the outcome of DEB-TACE seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As we know, the treatment of liver cancer is a comprehensive treatment. In any studies, DEB-TACE combined with radiofrequency ablation or sorafenib get better effect compared with DEB-TACE alone in liver cancer (49,50). In the future, DEB-TACE combined other treatment like SIRT, immunotherapy will get better overall response rate and overall survival in HCC.…”
Section: Discussionmentioning
confidence: 98%
“…As we know, the treatment of liver cancer is a comprehensive treatment. In any studies, DEB-TACE combined with radiofrequency ablation or sorafenib get better effect compared with DEB-TACE alone in liver cancer (49,50). In the future, DEB-TACE combined other treatment like SIRT, immunotherapy will get better overall response rate and overall survival in HCC.…”
Section: Discussionmentioning
confidence: 98%
“…A long-term follow-up observation of recurrent HCC with a diameter less than 5 cm showed that the 1-, 3-, and 5-year DFS rates after TACE combined with RFA treatment were 55.1%, 22.5%, and 9.7%, respectively, significantly higher than those after TACE treatment alone (41.1%, 9.9%, and 4.9%)[ 103 ]. A study of DEB-TACE combined with RFA for the treatment of recurrent HCC showed that the 1-, 2-, and 3-year OS rates were 90%, 82.3%, and 66.4%, respectively, percentages that were superior to those after surgical resection and RFA alone[ 104 ]. Compared with using RFA or TACE alone, combining the two methods has demonstrated advantages in the control of early and mid-stage recurrent HCC.…”
Section: Liver-targeted Local Therapy Still Dominatesmentioning
confidence: 99%
“…Zhang et al [ 46 ] demonstrated that DEB-TACE combined with RFA can increase the survival of patients with RHCC. Notably, OS rates were similar to primary HCC, while DFS rates were lower.…”
Section: Lrtmentioning
confidence: 99%